Chromosome-based genomics in the cereals - Doležel, Jaroslav; Kubaláková, Marie; Paux, Etienne; Bartoš, Jan; Feuillet, Catherina (Chromosome research, 2007)
The cereals are of enormous importance to mankind. Many of the major cereal species - specifically, wheat, barley, oat, rye, and maize - have large genomes. Early cytogenetics, genome analysis and genetic mapping in the cereals benefited greatly from their large chromosomes, and the allopolyploidy of wheat and oats that has allowed for the development of many precise cytogenetic stocks. In the genomics era, however, large genomes are disadvantageous. Sequencing large and complex genomes is expensive, and the assembly of genome sequence is hampered by a significant content of repetitive DNA and, in allopolyploids, by the presence of homoeologous genomes. Dissection of the genome into its component chromosomes and chromosome arms provides an elegant solution to these problems. In this review we illustrate how this can be achieved by flow cytometric sorting. We describe the development of methods for the preparation of intact chromosome suspensions from the major cereals, and their analysis and sorting using flow cytometry. We explain how difficulties in the discrimination of specific chromosomes and their arms can be overcome by exploiting extant cytogenetic stocks of polyploid wheat and oats, in particular chromosome deletion and alien addition lines. Finally, we discuss some of the applications of flow-sorted chromosomes, and present some examples demonstrating that a chromosome-based approach is advantageous for the analysis of the complex genomes of cereals, and that it can offer significant potential for the delivery of genome sequencing and gene cloning in these crops.
Keywords: cytogenetika; financování organizované; Chromosomes, Artificial, Bacterial; Sequence Analysis, DNA; Financing, Organized; Genomics; Chromosomes, Plant; Cytogenetics; sekvenční analýza DNA; Edible Grain; jedlá semena; Flow Cytometry; genová knihovna; umělé bakteriální chromozomy; průtoková cytometrie; chromozomy rostlin; Gene Library; genomika